Ex vivo COX‐1 and COX‐2 inhibition in equine blood by phenylbutazone, flunixin meglumine, meloxicam and firocoxib: Informing clinical NSAID selection. (15th April 2020) - Fogle, C.; Davis, J.; Yechuri, B.; Cordle, K.; Marshall, J.; Blikslager, A.
Summary: Newer cyclo‐oxygenase‐2 (COX‐2) selective nonsteroidal anti‐inflammatory drugs (NSAIDs), such as firocoxib, are proposed to reduce inhibition of cyclo‐oxygenase‐1 (COX‐1) and avoid undesirable side effects, while continuing to inhibit inflammation associated with COX‐2. However, COX selectivity is typically based on in vitro testing, which may not provide sufficient information critical for treatment selection. This study investigated the pharmacokinetics and ex vivo COX‐1 and COX‐2 inhibition of phenylbutazone, flunixin meglumine, meloxicam and firocoxib. Horses (n = 3) were administered one of the four drugs, in a randomised cross‐over design, with 3‐week washout periods. For each drug, three doses were given and sampling performed. Drug plasma concentrations, thromboxane B2 (TXB2 ) and prostaglandin E2 (PGE2 ) were determined. After one dose, TXB2 and PGE2 levels were significantly higher in horses administered firocoxib compared to flunixin meglumine. Following the third dose, TXB2 levels in horses administered firocoxib and meloxicam were significantly higher compared to flunixin meglumine or phenylbutazone; all drugs reduced PGE2 to a similar degree. The mean plasma half‐lives were 5.97 ± 0.47, 4.74 ± 0.14, 8.24 ± 3.74 and 47.42 ± 7.41 h for phenylbutazone, flunixin meglumine, meloxicam and firocoxib, respectively. Firocoxib and meloxicam exhibited significantly less COX‐1 inhibition compared to flunixin meglumine and phenylbutazone; all drugs inhibited COX‐2. The plasma half‐life of firocoxib was longer than the other NSAIDs, including meloxicam. Data from this study have important clinical relevance and should be used to inform practitioners' drug selection of a COX‐1 sparing or traditional NSAID and dose selection and to provide knowledge of the duration for the four NSAIDs studied.